Enhancement of dose response and nuclear magnetic resonance imaging of pagat polymer gel dosimeter by silver and platinum nanoparticles - Deyhimihaghighi, Najmeh (2014)
Radiotherapy is a treatment technique used to inactivate cancerous cells using ionizing radiation, typically of high-energy photons or electrons beam, which are delivered to the tumor volume without destroying the healthy surrounding tissues. The absorbed dose distributions in tissue volume can be studied in three dimensions (3D) by using a soft tissue equivalent polymer gel dosimeter, which centers on polymerization of monomers induced by free radicals as a result of radiolysis of water by ionizing radiation. In the presence of metal nanoparticles, the dose sensitivity of a polymer gel may be improved, from which its 3D dose distribution of nuclear magnetic resonance imaging (MRI) can be used in radiotherapy treatment plans. In the present study, the normoxic polyacrylamide gelatin and tetrakis hydroxyl methyl phosphoniun chloride (PAGAT) (4.5% N, N’-methylen-bis-acrylamide (bis), 4.5% acrylamid (AA), 5% gelatine, 5 mM tetrakis (hydroxymethyl) phosphonium chloride (THPC), 0.01 mM hydroquinone (HQ) and 86% deionized water) polymer gel dosimeters were synthesized with and without the presence of silver (Ag) and platinum (Pt) nanoparticles. The Ag nanoparticles with average particle sizes of 20 nm and particle concentration of 3.14×10-2 mg/l and Pt nanoparticles with average particle sizes of 10 nm and particle concentration of 1×10-2 mg/l were synthesized by laser ablation method from their respective metals in distilled water. The concentration of metal nanoparticles were varied from 3.14×10-2 to 9.42 ×10-2 mg/l for Ag nanoparticles and 0.5×10-2 to 3×10-2 mg/l for Pt nanoparticles to form two types of PAGAT polymer gel dosimeters before irradiating with 6 to 25 Gy of 1.25- MeV 60Co gamma rays. The predominant gamma rays interaction with matter is by Compton scattering effect as the photoelectric absorption effect is diminished. MRI evaluated the polymerization of the dosimeters and the gray scale of the MRI film was determined using an optical densitometer. The results of optical densities demonstrate that the amount of polymerization increased with an increase in absorbed dose, while the increase of depth inside the dosimeters has a reverse effect. Moreover, it was found that there was a significant increase in the optical density dose responds by 27.10% for dosimeters adding with 1×10-2 mg/l Pt nanoparticles and by 11.82% for dosimeters with 6.28 ×10-2 mg/l Ag nanoparticles.